Analysis of regional territories of the Visegrád Group between 2000 and 2016 - Torda, Márton; Járási, Éva Zsuzsanna; Péter, Balázs (Studia Mundi – Economica, 2020)
In our research we analyzed the changes of regional inequalities between the member states of the Visegrád Group from 2000 to 2016 by three economic indicators. These were compared by countries based on the Robin Hood index that can be used to analyze the distribution of economic goods (Bánfalvi, 2014). Initial values were collected from Eurostat database, further we also analyzed the Visegrád Group as a common economic area. Using the Lorenz curves of the three economic indicators (GDP, household income, employee wages) we calculated Robin Hood index which shows the difference from the perfectly even distribution in the case of household income, GDP or employee wages, for each country. In an extra calculation we also analyzed the Robin Hood indices calculated by the mentioned economic indicators for the 35 NUTS 2 regions of the Visegrád Group, managing the four countries as a common economic area. Our research aimed to find out, based on the used economic indicators, whether the inequalities in the distribution of goods between the regions of the Visegrád Group increased or decreased in the period from 2000 to 2016. Based on our analysis, we found that the values of some countries and some indicators show decreasing inequalities, however overall regional differences in the distribution of goods increased in the case of V4 countries, so was not managed to reduce regional differences in the analyzed economic indicators. Our research results can contribute to the development of the European Union's regional policy; the current governments of the four states of the Visegrad Alliance to reconsider the distribution of resources in the medium and long term; to identify the regions to be given priority support at regional level.